2012
DOI: 10.2478/s11756-012-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth, anatomy and enzyme activity changes in maize roots induced by treatment of seeds with low-temperature plasma

Abstract: Abstract:The seeds of Zea mays L. cv. KWS were exposed to low-temperature plasma (LTP) by using Diffuse Coplanar Surface Barrier Discharge (DCSBD) for 60 and 120 seconds respectively. Growth parameters, anatomy of roots and activity of some enzymes (CAT, G-POX, SOD and DHO) isolated from roots grown from the seeds treated by LTP were evaluated. Our results indicate that LTP treatment of maize seeds affects post-germination growth of seedlings and this effect depends on the duration of LTP treatment. LTP treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 40 publications
(38 reference statements)
5
103
0
Order By: Relevance
“…It was shown that the activity of peroxidase and catalase enzymes slightly increased following plasma treatment 22 . It is also reported that seed treated by plasma significantly increased the superoxide dismutase activity in maize 14 . Similar result was obtained for tomato 23 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It was shown that the activity of peroxidase and catalase enzymes slightly increased following plasma treatment 22 . It is also reported that seed treated by plasma significantly increased the superoxide dismutase activity in maize 14 . Similar result was obtained for tomato 23 .…”
Section: Discussionmentioning
confidence: 86%
“…At 180 s, absorption level of PAR was increased by 30% compared with the control (Table 6) which in turn increased photosynthesis rate and yield. Other researchers have also focused on the effects of plasma enhanced chlorophyll 14,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 mm. DCSBD has been used with positive results for treating of non-woven textiles [9], wood [10], silicon wafers [11], various foils and fibers [12][13][14], glass [7], metals [8] and bio-materials [15]. In the work presented here, the energy efficiency of DCSBD was estimated in order to improve the electrical circuit parameters of the DCSBD device, if necessary.…”
Section: Introductionmentioning
confidence: 99%
“…When a seed is treated with plasma, the plasma energy and active particles apparently transfer and penetrate through the seed coat because of the plasma's ability to penetrate through porous materials [20]. The interaction of cells with plasma might stimulate growth, alter protein structure, enhance enzymatic activities [21,22], thereby producing more functional metabolites. Plasma technology was also reported to increase the concentration of free radicals in seeds that play an important role in acceleration of seed metabolism [23].…”
Section: Gc-ms Analysis For Other Chemical Profilesmentioning
confidence: 99%